Representações sociais de professoras da educação infantil sobre alunos(as) das classes populares - Ribeiro, Andrea Porto (2017)
This study aimed to apprehend the meanings concerning to popular class students enrolled in preschool by identifying and analyzing the social representations f teachers in Child Education in the city of Uberlândia, Minas Gerais, Brazil. We collected data using questionnaires and interviews and they were organized and categorized according to the content analysis (BARDIN, 2009) and using Iramuteq software. The analysis was based on the theoretical and methodological framework of Social Representations as well on theories and practices in Popular Education. Five child schools have participated, one of each sectorial pole, aiming to decentralize the data collection, to obtain a heterogeneous sample, expressing the pedagogical ideology of the various spaces and subjects. The theoretical and methodological framework used to conduct research and data analysis aimed to ensure the coherence and the methodological rigor indispensable in the research on Popular Education and Social Representations. We considered the human dimension inherent to teaching, the power of the symbolic in guiding and justifying conduct and the human capacity to create and transform the world, others and oneself. It was possible to identify the representational structure and the meanings attributed to the educational actions with the popular classes and the influence of the socio-historical aspects and the capitalist strength in the organization of school space. The results indicated a conflicting relationship between family and school as well an ambiguous representation concerning to teaching and learning. The paradox indicated the complexities of teaching profession, the historical roots of the school the popular classes and teaching trajectory in Brazil. We considered that the context of popular classes schooling of popular classes continues marked by the marginalization, exclusion and oppression of the subjects that make up this social group. The teaching function at this crossroads presents the threads of a professional development conditioned to the structures imposed by the capital. Recognizing the constitutive elements of the educational reality in which teachers and students are found and considering in this perspective, the professional of Education as a historical subject whose life baggage interferes with their educational practice, we considered the urgent need for reflection and proposition of concrete actions for the strengthening of the public school and for the teacher training. It is indispensable to review the public educational policies, especially those directed to the initial and continued formation of teachers their valorization. Besides we pointed out the need of democratizing the popular participation in discussing such actions: it is fundamental to involve the subjects who participate in the school in the decision making about the administrative and pedagogical organization. From the research, we apprehended the meanings of the teachers’ representations on their students of popular classes; we understood that it was possible to identify these representations and their force in developing educative actions. We also identified the strong binding of these representations to the subjects’ life stories and the human mark through time in building meanings that we attribute to the others, to the world and to ourselves.